Blood and diamonds : Germany's imperial ambitions in Africa - Press, Steven (Harvard University Press, 2021)
"The history of mass-market diamonds goes back to German imperialism in Southwest Africa. Corporate power and state violence combined in the genocide of the Herero and Nama peoples, whose mineral-rich land supplied budding consumer demand in the United States. Steven Press makes clear that mass luxury has always come at a huge price."